On the Impact of COVID-19 on Crime in the US: Evidence from Maricopa County, Arizona and Los Angeles County, California - Bhuiyan, Suraiya Jabeen (Université d'Ottawa | University of Ottawa, 2020)
This paper investigates the short-term impact of COVID-19 and stay-at-home orders on crime in one Police Department in Maricopa, Arizona and three Police Departments in Los Angeles, California. Using daily data from Community Crime Map between January 2019 to June 2019 and January 2020 to June 2020, this paper finds that overall crime decreased by 0.4 percentage points during the pandemic. Using variation in the implementation of stay-at-home orders across the two states, this paper also finds that these policies led to a 1 percentage point decrease in overall crime. Conforming with anecdotal and empirical evidence, this paper finds heterogeneity across criminal offences. Analyzing the top 5 criminal offences in these two counties, it was seen that stay-at-home orders led to a statistically significant decrease in residential burglary and aggravated assault. However, these policies led to an increase in general theft, motor vehicle theft and commercial burglaries. The plausible channels through which COVID-19 impacts crime and explanations behind heterogeneity are discussed.